VO2 thin films and nanoparticles for energy-saving applications in architectural elements - Garcia, Ivan Aristides Ferreira (2016)
Vanadium dioxide (VO2) is a promising material with large interest in construction industry and architecture, due to its thermochromic properties. This material may be used to create "smart" coatings that result in improvements in the buildings energy efficiency, by reducing heat exchanges and, consequently, the need for acclimatization. In this work, VO2 thin films and coatings were produced and tested in laboratory, to apply in architectural elements, such as glass, rooftop tiles and exterior paints. Thin films were produced by RF magnetron sputtering and VO2 nanoparticles were obtained through hydrothermal synthesis, aiming to create "smart" windows and tiles, respectively. These coatings have demonstrated the capability to modulate the transmittance of infrared radiation by around 20%. The VO2 nanoparticle coatings were successfully applied on ceramic tiles. The critical temperature was reduced to around 40ºC by tungsten doping. Ultimately, two identical house models were built, in order to test the VO2 coatings, in real atmospheric conditions during one of the hottest months of the year, in Portugal – August.